Constructing Cooperation: Chinese Ontological Security Seeking in the South China Sea Dispute. Issue 4 (1st October 2016) - Curtis, Henry
Abstract: Chinese actions regarding disputes in the South China Sea have varied between complacence, use of force, and active engagement in attempts to forge cooperative relationships with disputant nations. In this paper, I argue that analysis of China's actions centered on the material and strategic importance of the Sea does not adequately account for the broad changes in China's behavior. Instead, I apply the theory of Ontological Security, arguing that changes in China's behavior in the dispute can best be explained as an attempt by China to maintain security of its national identity. In particular, I argue that China's historical understanding of its self, the expectations that arise from this, and the alignment of South East Asian state's actions with these expectations, inform China's attitude and actions in the dispute.